Energy Efficiency Opportunities and Savings Potential for Electric Motor and Its Impact on GHG Emissions Reduction - Molla Shahadat Hossain Lipu; Tahia Fahrin Karim (Institute of Advanced Engineering and Science, 2013)
Motors are the single largest users of electric power, consuming over half of all electricity and more than 60% of that used in the industrial sector. The use of energy-efficient motor technologies offers utilities the possibility of achieving substantial energy savings and reduction of GHG emissions. This paper presents a comprehensive literature review about energy efficiency opportunities and savings potential for electric motor. This paper compiles latest literatures in terms of journal articles, conference proceedings, web materials, reports, books, handbooks on electrical motor energy use, and opportunities for energy efficiency as well as energy savings strategies. Besides, present status of the efficient motor technology, market potential have been presented in this paper. Also, different energy savings strategies such as rewinding, use of variable speed drive (VSD), and capacitor bank to improve the power factor to reduce their energy uses have also been reviewed. Furthermore, cost parameters to carry out economic analysis and payback period for different energy savings strategies have been shown as well.DOI:http://dx.doi.org/10.11591/ijece.v3i4.3592